Vibration of submerged floating tunnels under asynchronous support excitation. (April 2021) - Akbarzadeh, Neda; Tariverdilo, Saeed; Emamyari, Alireza
Abstract: In recent years, submerged floating tunnels (SFT) have received considerable attention due to the growing increase of traffic volume and travel time. SFT provides eligible options for crossing long waterways. The long span of the SFT increases the probability of asynchronous excitation. This study examines the seismic behavior of the SFTs considering a) spatial variation of ground motion along the tunnel length, b) effect of different assumptions regarding this spatial variation, c) effect of of two- and three-dimensional modeling of fluid field. Two approaches including finite element and analytical solutions are used in the assessments. The results show that accounting for spatial variation of ground motion and three dimensionalities of the fluid field are detrimental in obtaining a realistic estimate of response parameters. Also, it is shown that using a linear approximation of spatial variation of ground motion along the tunnel length could give acceptable approximation of actual response.